NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU TEKS BAHASA INDONESIA KELAS X SMA - Aprilyanti Nurna Nengsi Ibrahim; Akmal Hamsa; Usman Usman (Fakultas Teknik Universitas Negeri Makassar, 2023)
Values of Character Education in Class X SMA Indonesian Textbooks. This study aims to describe the values and functions of character education in Class X SMA Indonesian textbooks. The type of research used is qualitative research with a causal approach in which any data obtained will be processed based on general ethical principles. This study uses a qualitative descriptive design. The results of the study showed that the values of character education contained in Indonesian language textbooks for Class X SMA, namely: religiosity, nationalism, integrity, independence, and mutual cooperation. While the functions of the values of character education, namely: faith, nobleness, health, knowledge, capability, creativity, independence, morality, and responsibility.